ADME of monoclonal antibody biotherapeutics: knowledge gaps and emerging tools. (August 2013) - Lee, Jean W
Absorption, distribution, metabolism and excretion (ADME) data are pivotal for small-molecule drug development, with well-developed in vitro and in vivo correlation tools and guidances from regulatory agencies. In the past two decades, monoclonal antibody (mAb) biotherapeutics have been successfully approved, including derived novel conjugates of active molecules (toxins or bioactive peptides) for specific target delivery or half-life extension. However, ADME information of mAb therapeutics lags behind that of small molecules due to the complex nature of the molecules and lack of appropriate tools to study drug exposure, biotransformation, and target engagement in the vascular and tissue spaces. In this perspective, the current knowledge gaps on ADME of mAb-related therapeutics are reviewed with potential solutions from emerging analytical technologies.